2008
DOI: 10.1002/anie.200803289
|View full text |Cite
|
Sign up to set email alerts
|

[(NHC)2Cu]X Complexes as Efficient Catalysts for Azide–Alkyne Click Chemistry at Low Catalyst Loadings

Abstract: La click, c'est chic! A catalytic system based on an [(NHC)2Cu]X complex (NHC=N‐heterocyclic carbene) was developed for the [3+2] cycloaddition of azides with alkynes under click conditions (see scheme). This system is broad in scope and highly efficient (turnover frequencies up to 5000 h−1) even at very low catalyst loadings (down to 40 ppm). Preliminary mechanistic studies suggest a specific precatalyst‐activation pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
125
1
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(132 citation statements)
references
References 40 publications
4
125
1
2
Order By: Relevance
“…The quotation marks on the section title are used to highlight this point. Diéz‐González and Nolan reported that, under neat conditions (i.e., no solvent), a cuprous/N‐heterocyclic carbene (NHC) complex ([ICy) 2 Cu]PF 6 ; Figure ) catalyzed triazole formation between benzyl azide and phenylacetylene in under 5 min (Scheme a) 9. It was an astonishingly fast reaction, which was driven in part by the high exothermicity of CuAAC under neat conditions—without solvent to dissipate the heat, the temperature of the reaction is expected to rise rapidly as the reaction proceeds 10…”
Section: “The Records”mentioning
confidence: 99%
See 1 more Smart Citation
“…The quotation marks on the section title are used to highlight this point. Diéz‐González and Nolan reported that, under neat conditions (i.e., no solvent), a cuprous/N‐heterocyclic carbene (NHC) complex ([ICy) 2 Cu]PF 6 ; Figure ) catalyzed triazole formation between benzyl azide and phenylacetylene in under 5 min (Scheme a) 9. It was an astonishingly fast reaction, which was driven in part by the high exothermicity of CuAAC under neat conditions—without solvent to dissipate the heat, the temperature of the reaction is expected to rise rapidly as the reaction proceeds 10…”
Section: “The Records”mentioning
confidence: 99%
“… a) Proton transfer directly from alkyne to triazolide; b) general base‐catalyzed proton transfer. B=NHC ligand,9 Et 3 N,30 or possibly ascorbate, acetate, and other carboxylates.…”
Section: Mechanismmentioning
confidence: 99%
“…It is worth to note that, in most cases explored in this work, there was no need of any additional base in the reaction medium as well as of any ligands for the catalytic system. 15,16 The selected benzoheterocyclic alkynes are S-propargyl derivatives of benzimidazole-2-thiol (1a), benzothiazole-2-thiol (1b) and benzoxazole-2-thiol (1c), N-propargyl derivatives of benzimidazole (1d) and phthalimide (1e). N-(3-Azidopropyl-and 4-azidobutyl) phthalimides (2a,b) were chosen as the phthalimide block.…”
Section: Introductionmentioning
confidence: 99%
“…Die Protonierung eines sogar noch basischeren Imidazol-2-yliden-Steuerliganden eines einkernigen Kupfer(I)-Komplexes durch Phenylacetylen wurde schon von Díez-Gonzµlez und Nolan beschrieben. [14] [23] Die beiden zentralen Kupfer(I)-Ionen werden von vier Acetylidliganden jeweils s-koordiniert und weisen je 18 VaSchema 2. Protonierung des zweikernigen CuAAC-Katalysatorkomplexes 1 mit EthylpropiolatzuCluster 2.E=CO 2 Et, Xyl = 3,5-Dimethylphenyl.…”
Section: Methodsunclassified